Factors predicting composite grafts survivability in patients with fingertip amputations; a systematic review and meta-analysis - Ali Mohamed Elameen; Asmaa Ali Dahy; Ahmed Abu-Elsoud; Amany Attalah Gad (Journal of Orthopaedic Surgery and Research)
Abstract Background Fingertip amputation is a commonly encountered injury in emergency settings. Composite grafting is a non-microsurgical alternative maintaining digit length with no donor site morbidities. This meta-analysis was conducted to retrieve factors associated with composite graft survivability among patients with fingertip amputations. Methods A literature review throughout twelve databases was performed on 24 July 2023. All clinical studies comparing the patients-related, trauma-related, or amputation-related variables among patients with survived and non-survived composite grafting were eligible for meta-analysis. Single-arm studies reported the potential predictors of composite graft survival among patients with fingertip injuries treated with composite grafting were included. Results This review included ten articles with 720 fingertips composite grafting. Of them, 526 grafts survived, with a pooled overall survivability of 72.8%. There was a significant association between younger age (OR 2.31,95%CI 1.10, 4.87, P = 0.03), level of amputation (I) (OR 0.31,95% CI 0.14 to 0.67, P = 0.003), and successful composite grafting. There was no statistically significant (P = 0.449) impact of time to composite grafting on the likelihood of composite graft survivability. Conclusion Composite grafting is a feasible and effective procedure for restoring aesthetically functional digits among patients with traumatically amputated fingertips. The composite graft survived among the majority of the patients, with a more significant survival pattern among younger populations and patients with more distal amputations. Level of evidence Level III.